AUDIT EVIDENCE COLLECTION METHODS AND INFORMATION SOURCES - Yeshpanov Islambek Toxtarbaevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article highlights the process of gathering audit evidence necessary to verify financial statements. It also provides detailed information on the implementation of the methods used in the collection of audit evidence in the process of auditing examination.